Association between dietary fat intake and colorectal adenoma in korean adults: A cross-sectional study. Issue 1 (January 2017) - Kim, Jeehyun; Oh, Seung-Won; Kim, Young-Sun; Kwon, Hyuktae; Joh, Hee-Kyung; Lee, Ji-Eun; Park, Danbee; Park, Jae-Hong; Ko, Ah-Ryoung; Kim, Ye-Ji
Abstract : Abstract: The incidence of colorectal cancer is rapidly increasing in South Korea. It is important to clarify the association between colorectal cancer and diet, being one of the main modifiable risk factors, as such studies in the Korean population are lacking. A cross-sectional study was performed using data from participants who had undergone a screening colonoscopy and a nutritional assessment during a routine health check-up from January 2008 to December 2011. Dietary intake data were derived from 1-day food records; colorectal adenoma was histopathologically confirmed by biopsy during colonoscopy. Eventually, 2604 participants were included in the analysis. The risk of colorectal adenoma by quintile of dietary fat intake was analyzed using logistic regression. Subgroup analyses by degree of risk and by location of colorectal adenoma were additionally performed. In men, total fat intake was not associated with risk of colorectal adenoma. However, risk of colorectal adenoma increased with higher saturated fatty acid (SFA) intake. The adjusted odds ratio in the highest quintile was 1.71 (95% confidence interval, 1.01–2.91) compared with that in the lowest quintile. There was no significant association between fat intake and risk of colorectal adenoma characterized by subsite. In female participants, total fat and specific fatty acid intake were not associated with risk of colorectal adenoma. These data support that high SFA intake is associated with risk of colorectal adenoma in Korean men.